Development of Partnership Based Marketing Strategy for Sustainable Tourism Villages in Kemiren Banyuwangi - Nahdi, Moehammad Robith; Winarno, Agung; Rahayu, Wening Patmi (MEC-J (Management and Economics Journal), 2025)
The development of tourism villages in Indonesia often faces challenges such as limited planning, weak stakeholder collaboration, suboptimal promotion, and low community participation. This study examines partnership-based marketing strategies in the Osing Kemiren Tourism Village, Banyuwangi Regency, and their influence on the growth of local MSMEs. Using a qualitative case study design, data were collected through in-depth interviews, observations, and documentation. The findings show that the pentahelix partnership involving local government, Pokdarwis/BUMDes, academic, travel agencies, mediacreates effective promotional synergy that enhances destination visibility and increases tourist visits. This collaboration strengthens MSMEs by improving sales, expanding market access, and encouraging long-term business sustainability. Overall, the study demonstrates that partnership-based marketing is an effective model for advancing tourism village development while supporting local economic empowerment.